Do Unethical Stocks Win in Developing Country? Evidence From Indonesia - Amalia, Farah; Prasetyaningrum, Ari Kristin; Fitriya Ardiani Aniqoh, Nur Aini (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
Ethical investing in various countries is increasingly popular following the number of ethical investors. However, the performance of ethical investments in many developed countries is lower than the performance of the opposite category, unethical stock, or researchers called it as sin stock. This study examines whether the performance of sin stocks in Indonesia is as good as the performance of sin stocks in developed countries considering the very different cultures and religions. This study comprehensively measures the performance of all sin stocks and ethical stocks using the risk-adjusted return approach, the Sharpe and Treynor ratios. To sharpen the analysis, this study also measures the efficiency of all types of stocks using the data envelopment analysis method. The results show that the performance of the sin stock portfolio in Indonesia is different from the facts in developed countries. Sin stocks in Indonesia had the worst performance during 2013-2022 compared to ethical stocks. Furthermore, in terms of efficiency, the SRI-Kehati Index has the highest score compared to all indices. This research contributes to provide theoretical and practical insights about the comparison of the performance of sin stocks and their counterparts in Indonesia which is different from sin stocks in developed countries. The originality of the research includes the creation of a sin stock portfolio and the use of constraint stocks as a proxy for ethical stocks.